The Study on Students’ Difficulties in Reading Comprehension at the 11th Grade of SMA Negeri 38 Maluku Tengah - Makaruku, Hendrik; Hukom, Salmon J.; Ferdinandus, Marcy Saartje; Hamsah, Siti Nurhayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to find out the difficulties faced by students in Reading Comprehension and the factors that influence these difficulties. The research subjects were 11th grade MIA SMA Negeri 38 Maluku Tengah, totaling 22 out of a total population of 37 students. The method used in this research is a quantitative descriptive method with data collection techniques in the form of tests and questionnaires. The results showed that students had difficulty in five main aspects of reading comprehension, namely determining the main idea 77%, making inferences 71%, finding specific information 44%, understanding vocabulary 41%, and identifying references 30%. Based on these results, the most difficult aspect for students is understanding vocabulary, with the highest percentage of errors at 77%. Meanwhile, six factors influence students to have difficulty in reading comprehension consisting limited vocabulary knowledge, lack of concentration while reading, lack of reading fluency, inadequate use of reading strategies, problem with processing information and low reading interest. This research is expected to make a positive contribution to students in improving reading comprehension, as well as to teachers in designing more effective and enjoyable learning strategies.